Shifting research culture to address the mismatch between where trials recruit and where populations with the most disease live: a qualitative study - Rai, T; Dixon, S; Ziebland, S (BMC, 2021)
Background: Research participation is beneficial to patients, clinicians and healthcare services. There is currently poor alignment between UK clinical research activity and local prevalence of disease. The National Institute of Health Research is keen to encourage chief investigators (CIs) to base their research activity in areas of high patient need, to support equity, efficiency and capacity building. We explored how CIs choose sites for their trials and suggest ways to encourage them to recruit from areas with the heaviest burden of disease.